The Effect of Competency and Work Discipline Supervision on Employee Work Effectiveness in The Police Karawang Resort - Nandang Zakaria; Kemal Taufik; Suhardi Suhardi (Dinasti International Journal of Management Science, 2026)
The purpose of this study is to analyze the influence of supervision on employee work effectiveness, analyze the influence of work discipline on employee work effectiveness, analyze the influence of supervision and work discipline simultaneously on employee work effectiveness at the Karawang Police Resort, the calculated t value for variable X1 (Supervision) is 7.758 while the t table value for n = 67 is 1.996. So t count > t table or 7.758 > 1.996, it can be concluded that partially the Coordination variable has an effect on employee work effectiveness, the calculated t value for variable X2 (Work discipline) is 10.258, while the t table value for n = 67 is 1.996. So t count > t table or 10.258 > 1.996 , it can be concluded that partially the Officer's Work Discipline variable influences employee work effectiveness, the R Square value is 0.899. This shows that 89.9% of Supervision and Work Discipline simultaneously (together) influence employee work effectiveness while the remaining 10.1% is influenced by other factors not examined in this study.